Metode Asessment Guru PAI Pada Perkembangan Karakter Moral Keagamaan Peserta Didik Di SMP Muhammadiyah Kupang - Kidi, Waisya; Musa, Muhajir (Prodi Pendidikan Agama Islam, 2023)
This study aims to find out 1) How is the assessment method carried out by PAI teachers at SMP Muhammadiyah Kupang whether it is in accordance with the assessment objectives set or not. 2.) How can the formation of religious moral character that should be a teacher but handed over to parents be able to develop optimally or not. This research uses a type of descriptive qualitative research with observation data collection techniques, interviews and documentation while the data analysis technique that the author uses is data reduction, data presentation or display and data conclusions. The results of this study indicate that the assessment method used by Islamic Religious Education teachers at SMP Muhammadiyah Kupang is dominantly carried out according to formative principles that are integrated with students in ongoing learning activities. And the development of the religious moral character of students at Kupang Muhammadiyah Middle School by instilling and strengthening the values ​​of the moral character of the Islamic religion by getting used to Duhah prayers and midday prayers and increasing religious activities and programs such as Islamic boarding schools and thafiz Qur'an.